Legal Aspects and Legal Implications of Auctioning Goods Via Social Media Platforms - Husein Simamora, Syahnan; Aji Hari Setiawan, Puguh; Hartana, Hartana (Devotion : Journal of Research and Community Service, 2026)
The rapid advancement of information technology in this era has driven people's need for information, which is increasingly diverse. In this context, Indonesia requires that every change take into account the social aspects of society. As explained by Soejono Soekanto, changes in the legal realm do not always occur simultaneously or simultaneously. This also indicates a gap that needs to be addressed in technology. The use of social media is not limited to activities but has also penetrated the business world, including the auction process. The increasingly easy access to online auctions through social media has also impacted issues related to information and communication technology, necessitating a method that can resolve and provide solutions to these issues. This research uses a normative juridical approach by examining laws and regulations, legal doctrine, and contract standards to address legal issues in the auction implementation system, specifically regulated in Minister of Finance Regulation No. 213/PMK.06/2020 concerning Auction Implementation Guidelines, one of the main regulations. These regulations relate to the legal basis and procedures, rights and obligations of the parties in the auction process.